Multidimensional study of ore deposits: Current status and future prospects - Huayong Chen; Jiamin Cheng; Junling Zhang (地质科技通报, 2022)
Since entering the 21st century, human society, including science and technology, has experienced dramatic changes in different fields. The ore deposit study has been continued for over 100 years, and many ore deposit models have been established based on numerous deposit case studies, which can be called the "single-dimension" study method. However, such modeling processes are being challenged by the need for further understanding of ore genesis and implications for mineral exploration. With the involvement of new technology such as big data and AI in geosciences, computing, simulation and big data mining are promoting ore deposit modeling to a new development stage. In the future, the experiments of ore-forming processes facilitated by computing and simulation, the mechanism and evolution of erosion and preservation of ore deposits, the genesis of ore formation using big data analysis and AI technology, together with the traditional ore deposit case studies, will form the new research frame of comprehensive ore deposit modeling, which indicates a transition from the current "single-dimension" study to a more robust "multiple-dimension" study of ore deposits.